Structure and Function of Fibrinogen: Insights from Dysfibrinogens - Matsuda, Michio; Sugo, Teruko; Yoshida, Nobuhiko; Terukina, Shigeharu; Yamazumi, Kensuke; Niwa, Kazuki; Maekawa, Hisato (Thrombosis and Haemostasis, 1999)
The structure-function relationships of dysfibrinogens and their clinical implications are discussed on the basis of the data provided from representative molecules.